Influence of Parental Involvement on Academic Achievement in Elementary School Children in Finland - Salonen, Vilma (International Journal of Psychology, 2024)
Purpose: The aim of the study was to analyze the influence of parental involvement on academic achievement in elementary school Children in Finland. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: A study on the influence of parental involvement on academic achievement in elementary school children in Finland found that active parental engagement positively impacts children's academic performance. Parents who were involved in their children's education, including helping with homework and attending school events, contributed to better academic outcomes. The research highlighted that children whose parents fostered a supportive learning environment at home showed higher levels of motivation and achievement. Additionally, the study emphasized the importance of communication between parents and teachers in creating a positive learning experience. Unique Contribution to Theory, Practice and Policy: Ecological systems theory, social capital theory & self-determination theory may be used to anchor future studies on the influence of parental involvement on academic achievement in elementary school Children in Finland. Schools should actively encourage and facilitate parental involvement in their children’s education, understanding that it can lead to improved academic outcomes. Policymakers should develop initiatives to support parental involvement in elementary education, such as providing funding for programs that strengthen school-family partnerships.